2010
DOI: 10.1007/s11033-010-0226-8
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and variations of the bovine myocyte enhancer factor 2C (MEF2C) gene promoter in Bos Taurus cattle

Abstract: Myocyte Enhancer Factor 2 (MEF2) proteins are a small family of transcription factors that play pivotal role in morphogenesis and myogenesis of skeletal, cardiac, and smooth muscle cells. In vertebrates, there are four MEF2 genes, referred to as MEF2A, -B, -C, and -D, that are located on different chromosomes. After birth MEF2A, MEF2B, MEF2D transcriptions are expressed ubiquitously, whereas MEF2C transcripts are restricted to skeletal muscle, brain, and spleen. In this study, on the basis of the sequences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Recently, Zhou et al (2010) described three SNPs in 5¢-UTR, exon 4, and intron of the chicken MEF2A gene. In our previous study, we found in the bovine Mef2C gene two substitutions and two InDels upstream from the putative transcription start of exon 1 that were deposited in the GenBank database ( Juszczuk-Kubiak et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhou et al (2010) described three SNPs in 5¢-UTR, exon 4, and intron of the chicken MEF2A gene. In our previous study, we found in the bovine Mef2C gene two substitutions and two InDels upstream from the putative transcription start of exon 1 that were deposited in the GenBank database ( Juszczuk-Kubiak et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Homologous ESTs of pig were available from GenBank using a BLASTN program based on cattle Mef2c gene sequence . Genomic DNA template was prepared from blood of a Meishan pig.…”
Section: Methodsmentioning
confidence: 99%
“…Many of the same transcription factors (TFs) that control embryonic myogenesis are redeployed during adult regenerative myogenesis. Myocyte enhancer factor 2 (MEF2) is a family of TFs that plays a crucial role in myogenesis of skeletal, cardiac, and smooth muscle and is essential for muscle differentiation . In vertebrates, this family has four members: MEF2A, MEF2B, MEF2C, and MEF2D .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several SNPs in the MEF2A gene, which were associated with body and muscle weight, have been reported in cattle (Chen et al, 2010) and chickens (Zhou et al, 2010). Recently, five new SNPs in the promoter region and intron 1 of the bovine MEF2C gene (Juszczuk-Kubiak et al, 2011), as well as three SNPs in the promoter region of the MEF2A gene (Juszczuk-Kubiak et al, 2012a), have been reported. In neither case was association of the SNPs with carcass traits studied, but a significant effect of the promoter variants on the MEF2A mRNA level in the LD muscle of young Polish Holstein-Friesian bulls was shown.…”
mentioning
confidence: 99%